THE IMMUNE RESPONSE IN WORM INFECTION AT PUSKESMAS TANJUNG KARANG IN MATARAM - Gunarti Gunarti; Erlin Yustin Tatontos; Urip Urip (Jurnal Kesehatan Prima, 2018)
Abstrac: A worm infection can decrease sufferers’ health condition, nutrition, intelligence and their productivity thus, it can cause numerous of disadvantages economically. The immune response to worm infection begins with Th2 activation with a significant increase of IL-4, IL-5, IL-9, IL-10 and IL-13. The cytokines IL-5 that formed stimulates the growth and activation of eosinophils. The purpose of this research was to know the immune response by increasing the number of eosinophils to worm infection rate at Puskesmas Tanjung Karang. The research design was expost facto with cross sectional or transversal. The sample was communities’ faces and blood at Puskesmas Tanjung Karang as many as 50 people. The technique sampling was random from family members who have worm risk factors (poor sanitation conditions, living near animal cage, ground floor houses, pets such as dogs and cats). The correlation analysis of worm infection with eosinophils used Mann Whitney Test. The results showed that the prevalence of worm infection belong to mild category for Trichurin trichura was 10%, and the overall worm infection was 12% whereas the average number of eosinophils in the normal category was between 50-300 cells / mm². The results of statistical analysis were not significant (Asymp. Sig. 0.059) which means that there was no effect of the immune response with the number of eosinophils on the level of worminfection at Puskesmas Tanjung Karang.Keywords: Immune response, eosinophil, worm infection.